DOI: 10.31274/etd-180810-673
|View full text |Cite
|
Sign up to set email alerts
|

E-learning: Investigating students' acceptance of online learning in hospitality programs.

Abstract: A special thank you goes to my major professor, Dr. Robert Bosselman. In spite of having very busy schedule as Chair of Apparel, Educational Study, and Hospitality Management (AESHM), Dr. Bosselman guided me by providing constructive comments and suggestions to assist me in deciding my sample, distributing and collecting data, and writing my research paper. Without Dr. Bosselman's immediate feedback, patience, and positive expectations toward me, I could not have successfully completed this project.My apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 159 publications
(220 reference statements)
3
20
0
1
Order By: Relevance
“…Ref. [21] examined the effects of perceived interaction, perceived infrastructure and perceived usefulness (PU) on satisfaction (CS), and the effects of them on online learning continuance intention (e-loyalty). The study showed a significant amount of variance in online learning satisfaction and e-loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [21] examined the effects of perceived interaction, perceived infrastructure and perceived usefulness (PU) on satisfaction (CS), and the effects of them on online learning continuance intention (e-loyalty). The study showed a significant amount of variance in online learning satisfaction and e-loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Song (2010) strengthened the critical need of e-learning which is highly associated with the technology application, as such learners" technology acceptance will play a crucial part in contributing to the success of online learning programs. This study, viewed acceptance in the context of acceptance of technology which refers to online courses which users adapt to, as well as the service as a useful tool in improving their performance in learning.…”
Section: Acceptancementioning
confidence: 99%
“…Previous researchers such as , Song (2010) & Selim (2007 states that the role of lecturers (expertise, active participation, skills, support) and course design (user-friendly, flexible, easy-to-use, updated and relevant) is important and can contributes to student satisfaction. However, the results of this study found that three elements in the expectation components such as self-directed learning, interaction quality between students and peers and course design quality can give positive effects on satisfaction towards e-learning.…”
Section: Findings and Discussionmentioning
confidence: 99%